PENDEKATAN KESEIMBANGAN JANGKA PANJANG NILAITUKAR MATA UANG RUPIAH TERHADAP DOLAR AMERIKA (1973-1997) - Rahayu, Siti Aisyah Tri (Universitas Muhammdaiyah Surakarta, 2004)
The aims of this paper is to test Purchasing Power Parity for Indonesian currency to US dollar. The analysis used in this article is the long run equilibrium with cointegrated test approach.The result show that almost all variable in this model are stasionair in the first degree, but both variable s and p not cointegrated for the absolut PPP. The estimated result show that Pj=l hypothesis is not hold during 1974.4 -1998.3 period. In the other hand, cointegrated test for the variable dst and dpt in the relative PPP is cointegrated and the estimation result show that the Relative PPP and the Cochrane-orcutt model PPP is hold for Indonesia, except for the period when Indonesia had fixed exchange rates during 1974.4 -1986.3Â period.